Peta Konflik dan Konflik Kekerasan di Minangkabau Sumatera Barat - Zubir, Zaiyardam; Zayzda, Nurul Azizah (Masyarakat Indonesia, 2010)
The democratic transition from the New Order Regime towards the Reform Era was followed by a series of ethnic and religious conflicts in several regions. These conflicts appeared not only at the grassroots but also at the politicians’ and government’s levels. This article explains the map, the causes and the forms of the conflicts within the Minangkabau, society in West Sumatra. Minangkabau society is one of the ethnic groups in Indonesia that consists of two regions (darek-rantau), with a matrilineal system known as orthodox Moslems that believes to the prophecy “Adat Bersendi Syarak, Syarak Bersendi Kitabullah”. This article analyses the question of why during the Reform era the numbers of conflict in West Sumatra increased with high intensity. If the Paderi War history with its conflicts and violence aspects are inherent within the Minangkabau society, is there any mechanism within the local wisdom to solce these conflicts?